Request Book and Article System (RBAS): tools, techniques and outcomes / Hasniza Amno … [et al.] - Amno, Hasniza; Ali, Rugayah; Abd Rahim, Nur Hanida; Zainol, Zulkifli; Mat Nashir, Waheeda; Abd Jais, Nurul Huda; M Zin, Hafiz (2020)
Request Book and Article System (RBAS) is a web-based system for online interlibrary book loan and article request. The system was developed in 2019 using a Linux-based/Window server operating system with Apache 2.4 and PHP 7.0/MySQL databases. The new system integrates the interlibrary loan process and document delivery services. The system is currently being used at Advanced Medical and Dental Institute (AMDI), Universiti Sains Malaysia, Kepala Batas, Pulau Pinang which is an advanced academic institute with an interconnected research, and clinical ecosystem. Previously, records of AMDI library request, reports and storage was handled manually and resulted in complex workflows. The internal or external library users use the RBAS via AMDI Library website to request for books or articles from the library. Their request is transmitted through the system and is automatically placed in the queue. RBAS enables users to view request, view document, updating status from within the system and produces comprehensive reports and statistics. For a book request, the user may receive an email providing standard message of their book request status from RBAS. Meanwhile, for article request, the system delivers the document or files automatically to the requestor email account and tracks the supply status. Thus, it helps to improve books and articles request management processes and improves the turnaround times for users. The system also reduces the administrative staff requirements in a library. The feedbacks of the implementation of this new workflows and processes were collected through a customer satisfaction survey. The online system is found to be advantageous due to its simplicity and streamlining interlibrary loan and document delivery workflows. RBAS is a unique in-house system; which is flexible and can be designed to be to fit the organisation’s purposes with no extra investment. RBAS copyright registration number is LY202000668.